Evaluating Emergency Department Resource Capacity Using Simulation - Norazura, Ahmad; Noraida, Abdul Ghani; Anton Abdulbasah, Kamil; Razman, Mat Tahar; Aik Howe, Teo (Canadian Center of Science and Education, 2012)
Emergency departments open 24 hours every day and may receive patients at any time most unexpectedly. Adequate resource planning to meet the various demands in emergency departments is arguably amongst the most critical challenges faced by hospital administrators due to the complexity of the system and diverse patient flows. In this paper, we present a computer simulation model to evaluate resource utilization among personnel and physical resources in a typical emergency department (ED) of a government hospital in Malaysia. The model allows administrators to see patient movement flows as well as how these flows are affected by resource capacity level in the ED. The use of this simulation model helps to evaluate ED operations, provides useful insight for possible areas of improvement, and directs the allocation of specific resources for maximal impact. Three scenarios were tested to find out the impact of patient surge on ED performance measures. Results from the scenarios show that a 30% increase of attendances according to triage zones affects most of the performance measures. In addition, medical assistants are the critical resources with average utilization greater than 70%.